2022
DOI: 10.1021/acs.energyfuels.2c01006
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Machine Learning Research for Nanofluid-Based Heat Transfer in Renewable Energy System

Abstract: Nanofluids have gained significant popularity in the field of sustainable and renewable energy systems. The heat transfer capacity of the working fluid has a huge impact on the efficiency of the renewable energy system. The addition of a small amount of high thermal conductivity solid nanoparticles to a base fluid improves heat transfer. Even though a large amount of research data is available in the literature, some results are contradictory. Many influencing factors, as well as nonlinearity and refutations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(81 citation statements)
references
References 334 publications
0
56
0
Order By: Relevance
“…From the result it is revealed that the COF of GFRPA66 with 35 wt.% is low as compared with GFRPA66 with 30 wt.% reinforcements, since it has better transfer layer formation, increased adhesion of PA66, and low abrasion by glass fiber with less temperature between the contact surfaces. Also the elastic modulus and ultimate strength of glass fiber improve as the weight of glass fiber increases [ 70 , 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…From the result it is revealed that the COF of GFRPA66 with 35 wt.% is low as compared with GFRPA66 with 30 wt.% reinforcements, since it has better transfer layer formation, increased adhesion of PA66, and low abrasion by glass fiber with less temperature between the contact surfaces. Also the elastic modulus and ultimate strength of glass fiber improve as the weight of glass fiber increases [ 70 , 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since GP and SVM-Schotastic model performed the best among the other models for FS and CS for this dataset, sensitivity analysis was carried out on it by changing the input combination and taking out one input parameter at a time, as shown in Table 9 and Table 10 . Statistical assessment metrics such as CC, MAE, and RMSE were used to assess each model’s performance [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Table 9 and Table 10 , demonstrates that the number of curing days followed by CA, C, w and MP is critical in predicting the flexural and compressive strength of a concrete mix.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Table 9 and Table 10 , demonstrates that the number of curing days followed by CA, C, w and MP is critical in predicting the flexural and compressive strength of a concrete mix. Due to the pozzolanic reactions, concrete recovers 60% of its strength after 7 days of curing and increases by 99% after 28 days, resulting in a low CC value after removing the aforementioned characteristic [ 76 , 77 , 78 , 79 ]. The pozzolanic reaction is a slow process, and as the curing period lengthens, the amount of gel produced in the mix increases, resulting in greater strength [ 65 ].…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Global warming as a consequence of burning fossil fuels has encouraged researchers to explore, design, and optimize alternative renewable energy technologies. The establishment of sustainable energy sectors aims to decrease greenhouse gas (GHG) emissions and thus reduce global warming to well below 2 °C to align with the goals set out in the Kyoto Protocol and the Paris Agreement . In this approach, thermoelectric generators (TEGs) have shown promising capabilities in recovering the low-grade waste energy. This technology is an effective method employed to take full advantage of using wasted thermal energy to improve the efficiency of clean energy sources, such as solar and geothermal.…”
Section: Introductionmentioning
confidence: 99%